EFFICACY OF CHLORINE DIOXIDE ON ORAL LESIONS IN ACUTE MYELOBLASTIC LEUKEMIA PATIENTS UNDERGOING CHEMOTHERAPY - RIDHO, FAIZNUR; FITRIASARI, NURI; ZAKIAWATI, DEWI (International Journal of Applied Pharmaceutics, 2023)
Objective: The aim of this study was to describe the pharmacological management of oral lesions, particularly using chlorine dioxide agents in an acute myeloblastic leukemia (AML) patient undergoing chemotherapy. Methods: A 9 y old girl was referred from the Department of Paediatrics at Hasan Sadikin Hospital to the Department of Oral Medicine with complaints of swelling on the lips, difficulty while eating, swallowing, and even opening the mouth. Extra oral examination showed angioedema on the lips with a prominent serosanguinolent crust. Intraoral examination revealed white plaques that could not be scrapped off in all parts of the mouth. The patient was diagnosed with AML and had received chemotherapy until the second cycle. Results: Gauze soaked in chlorine dioxide oral rinse was applied to compress the patient's lips. Following this, 0.2% hyaluronic acid gel was also administered. In terms of intraoral treatment, chlorine dioxide was also applied by spraying it throughout the entire mouth. After one month, the lesion had completely healed, allowing the patient to open their mouth without any issues. Conclusion: Chlorine dioxide significantly improves the oral mucosal lesions in an AML patient undergoing chemotherapy.